2022
DOI: 10.1021/jacs.2c02073
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Grafting to Polydopamine Free Radicals for Universal Surface Functionalization

Abstract: Modifying surfaces using free radical polymerization (FRP) offers a means to incorporate the diverse physicochemical properties of vinyl polymers onto new materials. Here, we harness the universal surface attachment of polydopamine (PDA) to “prime” a range of different surfaces for free radical polymer attachment, including glass, cotton, paper, sponge, and stainless steel. We show that the intrinsic free radical species present in PDA can serve as an anchor point for subsequent attachment of propagating vinyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…Combined with the above Ni 2p and Co 2p XPS results, the metal oxide should be mainly attributed to CoO species owing to the oxophilic property of Co. X‐band electron paramagnetic resonance (EPR) spectroscopy was also performed for Ni 1 Co 1 /C (Figure 2D). A single‐line asymmetric resonance signal at g = 2.001 was clearly observed, which can be assigned to the carbon‐centered radical in the sp 2 carbon‐related dangling bonds of the free‐carbon phase 40–42 . This carbon‐centered radical might be associated with cationic defects within the carbon backbone, which can accept electrons to improve the electronic interaction with reactants and thus improve the catalytic performance of Ni 1 Co 1 /C 43 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Combined with the above Ni 2p and Co 2p XPS results, the metal oxide should be mainly attributed to CoO species owing to the oxophilic property of Co. X‐band electron paramagnetic resonance (EPR) spectroscopy was also performed for Ni 1 Co 1 /C (Figure 2D). A single‐line asymmetric resonance signal at g = 2.001 was clearly observed, which can be assigned to the carbon‐centered radical in the sp 2 carbon‐related dangling bonds of the free‐carbon phase 40–42 . This carbon‐centered radical might be associated with cationic defects within the carbon backbone, which can accept electrons to improve the electronic interaction with reactants and thus improve the catalytic performance of Ni 1 Co 1 /C 43 …”
Section: Resultsmentioning
confidence: 95%
“…A single-line asymmetric resonance signal at g = 2.001 was clearly observed, which can be assigned to the carbon-centered radical in the sp 2 carbon-related dangling bonds of the free-carbon phase. [40][41][42] This carbon-centered radical might be associated with cationic defects within the carbon backbone, which can accept electrons to improve the electronic interaction with reactants and thus improve the catalytic per- S1 and S2). S4).…”
Section: Physicochemical Properties Of Catalystsmentioning
confidence: 99%
“…Furthermore, Nothling et al showed how PDA works as an anchor point for the attachment of propagating vinyl polymer macroradicals through radical-radical coupling. [98] The process further [95] Copyright 2022, Elsevier. b) (Left) Optical images of a PDA membrane subjected to light-induced contraction at ambient conditions.…”
Section: Pda-based Filmmentioning
confidence: 99%
“…Furthermore, Nothling et al showed how PDA works as an anchor point for the attachment of propagating vinyl polymer macroradicals through radical–radical coupling. [ 98 ] The process further enhances the rich chemistry of PDA and expands its potential for the functionalization of multiple surfaces.…”
Section: Recent Advancements In Pda Compositesmentioning
confidence: 99%
“…15 It is also identied as a small-molecule mimic of mussel foot proteins, which can undergo autooxidation and then selfpolymerize under alkaline conditions to generate polydopamine (PDA) materials. [15][16][17][18][19][20][21][22] DA derivatives and PDAincorporated hydrogels exhibit strong adhesiveness toward various organic and inorganic substrate surfaces, and human skin. [8][9][10][11][12] Radical polymerization using additional initiators is a typical method to prepare mussel-inspired hydrogels.…”
Section: Introductionmentioning
confidence: 99%